Review on the Diseases and Insects of Lycium barbarum L - Yanting, Cao; Jianli, Liu (Plant Diseases and Pests(植物病虫害研究：英文版), 2014)
With the increasing planting area of Lycium barbarum L. , influence of diseases and pests has grown more serious, and the researches on the diseases and pests of L. barbarum L. have become increasingly important. This study reviewed the found diseases and pests of L barbarum L. and corresponding control measures, proposed the problems, suggestions and prospects, in order to provide references for the sustainable healthy development of L. barbarum L. industry in the Ningxia Hui Autonomous Region.